Recombination in the wheat stem rust pathogen mediated by an indigenous barberry species in Spain - Rodriguez-Algaba, Julian; Villegas, Dolors; Cantero-Martínez, Carlos; Patpour, Mehran; Berlin, Anna; Hovmøller, Mogens S.; Jin, Yue; Justesen, Annemarie F. (Frontiers in Plant Science, 2024)
The comeback of wheat stem rust in Europe, caused by Puccinia graminis f. sp. tritici, and the prevalence of the alternate (sexual) host in local areas have recently regained attention as a potential threat to European wheat production. The aim of this study was to investigate a potential epidemiological link between the aecia found on an indigenous barberry species and stem rust infections on nearby cereals and grasses. Aecial infections collected from Berberis vulgaris subsp. seroi were inoculated on a panel of susceptible genotypes of major cereal crop species. In total, 67 stem rust progeny isolates were recovered from wheat (51), barley (7), and rye ( 9), but none from oat, indicating the potential of barberry derived isolates to infect multiple cereals. Molecular genotyping of the progeny isolates and 20 cereal and grass stem rust samples collected at the same locations and year, revealed a clear genetic relatedness between the progeny isolated from barberry and the stem rust infections found on nearby cereal and grass hosts. Analysis of Molecular Variance indicated that variation between the stem rust populations accounted for only 1%. A Principal Components Analysis using the 62 detected multilocus genotypes also demonstrated a low degree of genetic variation among isolates belonging to the two stem rust populations. Lastly, pairwise comparisons based on fixation index (Fst), Nei's genetic distances and number of effective migrants (Nm) revealed low genetic differentiation and high genetic exchange between the two populations. Our results demonstrated a direct epidemiological link and functionality of an indigenous barberry species as the sexual host of P. graminis in Spain, a factor that should be considered when designing future strategies to prevent stem rust in Europe and beyond.